2016
DOI: 10.2174/1389201017666160519113104
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of Drug-Loaded Hydrogels for Application in Osteosarcoma Treatment

Abstract: This is a literature review of studies focusing on the preparation of hydrogels for use as oncological drug delivery systems in the treatment of osteosarcoma (OS). The databases of the US National Library of Medicine National Institutes of Health, Embase, OVID, and Cochrane Library, and the references of retrieved studies, were traced from 1843 to December 21, 2015, without language restrictions. The obtained data were evaluated by complementary statistical methods. Potentially relevant studies were found and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Studies by Lijmer et al [11, 12] were used to determine the proof level of the studies. All bibliographies were also reviewed and reference lists were re-evaluated to find appropriate articles.…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Lijmer et al [11, 12] were used to determine the proof level of the studies. All bibliographies were also reviewed and reference lists were re-evaluated to find appropriate articles.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing sophistication of hydrogel-based models can be achieved through a combination of chemical engineering and biologic layering, including the construction of soluble mediator (growth factors, chemokines, peptidyl signaling molecules) gradients or combinatorial co-culturing of cancer cells with stromal cells including endothelial cells, fibroblasts, and immune cells. While hydrogels have been explored as a controlled drug release scaffold strategies for OS therapy (156)(157)(158), the study 3D scaffold tumor models for unraveling OS biology and metastasis remains limited, with some investigations describing differences in behavioral phenotype of malignant OS cells compared to non-transformed osteoblasts based upon matrix rigidity and elasticity (159,160). In addition to hydrogel scaffolds, chitosan, silk, and synthetic polymers have served as adhesive constructs for 3D OS modeling and have illuminated mechanisms behind viral permissiveness (161), hypoxia-induced angiogenic mediator secretions (162), drug resistance (163), and maintenance of stem cell phenotype (164).…”
Section: Scaffold-based 3d Modelsmentioning
confidence: 99%
“…The percentage distribution of articles by year was recorded, and the evidence level was determined according to Lijmer et al 23,24 Bibliographies thought to be missed during the database research were examined again. Unpublished grey literature, including articles, comments, letters, editorials, protocols, guides, meta-analyses and collections were not included.…”
Section: Search Strategymentioning
confidence: 99%
“…Nevertheless, it is important for such data to be compiled and compared. 24 The studies included in the present review did not provide common data and therefore homogeneity or heterogeneity tests could not be performed. As a result of this study, it can be concluded that the hypothesis that there is only one real underlying effect that to be predicted cannot be justified statistically.…”
Section: -2234mentioning
confidence: 99%